Synthesis, Spectral Characterization and Bioactivity of Co(II), Mn(II), Fe(II) and Fe(III) Complexes of Bidentate N,S Schiff Base of S-Benzyl Dithiocarbazate with p-(Dimethylamino)benzaldehyde - V. Junghare, Nilesh; B. Jagtap, Shrikant; R. Jadhav, Rahul; P. Jadhav, Jyoti (Asian Journal of Chemistry, 2022)
Metal complexes of (ML2)X2 type (X = H2O) of Co(II), Mn(II), Fe(II) and Fe(III) (X is NO3– and H2O) were synthesized using Schiff base, S-benzyl-β-N-(p-dimethylaminophenyl)methylene dithiocarbazate (HL), which was synthesized by the condensation of equimolar concentrations of p-(dimethylamino)benzaldehyde and S-benzyldithiocarbazate. The metal complexes and dithiocarbazate ligands were confirmed by elemental study and spectroscopic techniques such as 1H and 13C NMR, electronic absorption spectroscopy, molar conductance, infrared techniques. The magnetic susceptibility and UV-vis spectral data suggest that the metal complexes (ML2)X2 show octahedral geometry. The bioactivity of ligand and its metal complexes were investigated by the well diffusion method against one fungus (Candida albicans) and three pathogenic bacteria (E. coli and B. cereus and S. aureus). Bioactivity analysis revealed that the (ML2)X2 complex of Fe(II) and Fe(III) shows enhanced antibacterial activity than free ligand. Comparatively, among all metal complexes, the Fe(III) complex shows higher antibacterial activity and moderate antifungal activity.